2023
DOI: 10.1161/jaha.122.028015
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Elastic Properties of the Ascending Aorta in Fetuses With Coarctation of the Aorta

Abstract: Background Abnormal aortic elastic properties are major notable vasculopathy involved in coarctation of the aorta (CoA). However, there are no reports on aortic wall elastic characteristics in fetuses with CoA. Methods and Results Fifty‐six fetuses with CoA and 56 normal controls were included in this prospective case–control study. The dimensions of the cardiac chamber, the size of the aorta, left ventricular myocardial performance index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
3
3
0
Order By: Relevance
“…33 Fetal HQ can determine LV-FAC, RV-FAC, LV-LS, and RV-LS and divide the ventricles into 24 segments and analyze each segment's FS changes. This study shows that when compared with the control group, the left ventricle's overall systolic function, longitudinal contractile function, and lateral contractile function were inhibited in fetuses in the CoA group, whereas these parameters were inhibited in the right ventricle's basal and middle segments, which is consistent with the findings of DeVore et al 21,22 Xu et al 34 reported reduced fetal ventricular FAC in the CoA group, and a study by Liu et al 26 that involved 122 fetuses with CoA reported that LV-FAC and LV-LS were reduced in fetuses with CoA, although there were no significant changes in RV-FAC and RV-LS. Fetal cardiomyocytes are susceptible to hypoxia, which leads to sarcomere shortening in myocardial cells, which are an important component of myocardial contraction.…”
Section: Discussionsupporting
confidence: 91%
“…33 Fetal HQ can determine LV-FAC, RV-FAC, LV-LS, and RV-LS and divide the ventricles into 24 segments and analyze each segment's FS changes. This study shows that when compared with the control group, the left ventricle's overall systolic function, longitudinal contractile function, and lateral contractile function were inhibited in fetuses in the CoA group, whereas these parameters were inhibited in the right ventricle's basal and middle segments, which is consistent with the findings of DeVore et al 21,22 Xu et al 34 reported reduced fetal ventricular FAC in the CoA group, and a study by Liu et al 26 that involved 122 fetuses with CoA reported that LV-FAC and LV-LS were reduced in fetuses with CoA, although there were no significant changes in RV-FAC and RV-LS. Fetal cardiomyocytes are susceptible to hypoxia, which leads to sarcomere shortening in myocardial cells, which are an important component of myocardial contraction.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is similar to that in a previous study by Vyas et al in which fetuses with hypoplastic left heart syndrome presented decreased MPI 30 . Altered MPI in the fetuses with CoA is also consistent with another study by our team on fetal aortic elastic properties 31 . Previous studies have put forth the proposition that the impaired myocardial deformation observed in fetuses with CoA may be attributed to abnormal intrinsic myocardial structure 32,33 .…”
Section: Discussionsupporting
confidence: 87%
“…23 Our previous study showed impaired aortic elastic properties in fetuses with CoA. 31 Abnormal aortic stiffness and left ventricular outflow tract orientation may affect vortex flow in the aorta. Though no significant correlation was found between LV vortex geometry and aortic isthmus size, additional research is needed to evaluate the relationship between vortex flow and left ventricular outflow tract orientation, as well as aortic elastic properties in CoA.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations